JURIDICAL ANALYSIS OF POACHING USING ASSEMBLED FIREARMS IN FOREST AREAS IN RELATION TO EMERGENCY LAW NUMBER 12 OF 1951 (STBL.1948.NO.17) (STUDY OF SPECIAL CRIMINAL DECISION: 115/PID.SUS/2019/PN.KNG) - Dewi, Maftuhah (FOCUS: Jurnal of Law, 2024)
Many crime models in the world originate from assembled firearms. The purpose of this research is to juridically analyze the perpetrators of illegal hunting using assembled firearms in connection with Emergency Law number 12 of 1951. The method used uses normative research with primary data from the main literature law and secondary additional literature related to data categorization. The data obtained is reduced, displayed and conclusions are drawn. Validation through triangulation and content analysis. The findings of law enforcement against poaching using homemade firearms in Mount Ciremai National Park face various complex challenges. Although there are laws governing firearm ownership, their implementation is often hampered by various factors, including limited resources and clever tactics used by perpetrators. This study recommends the need to revise outdated laws and improve the firearms licensing and monitoring system.